Bacteriological Quality and Heavy Metal Analysis of Packaged Water Produced in Lusaka, Zambia and Associated Quality Control Measures - Banda, Rodney K.; Mubita, Patricia; Moonga, Given; Meki, Chisala D. (Frontiers in Public Health, 2021)
Many people in the world lack safe basic drinking water sources and rely on untreated water source. Packaged water can be considered as an alternative to other water sources if measures are put in place to ensure its safety for consumption. This study aimed to assess the bacteriological and chemical quality of packaged water produced in Lusaka, Zambia and associated quality control measures. A cross-sectional study was conducted in May 2019 where 18 brands of packaged water were analyzed for total and feacal coliforms as well as concentrations of Lead, Chromium and Cadmium. The study found that 33.5% of the packaged water produced in Lusaka did not comply with the standard for drinking water on bacteriological quality. We also found that the concentrations for Lead were less than 0.01mg/l in all the 17 samples, thus compliant to WHO/ZABS standards. Concentrations of Chromium were between 0.002mg/l and 0.62mg/l and compliance to the standard was 11.8%. Concentrations for Cadmium were as low as 0.009mg/l and as high as 0.2mg/l as such, non-compliant. Most brands of the packaged water did not conform to the bacteriological standards for drinking water and none of the brands conformed to the chemical quality.